2010
DOI: 10.1016/j.diagmicrobio.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Pathotypes of diarrheagenic Escherichia coli in children attending a tertiary care hospital in South India

Abstract: The prevalence of diarrheagenic Escherichia coli (DEC) in children under 5 years was studied in children with diarrhea and controls in South India. Four polymerase chain reaction (PCR) “schemes” were used to detect genes of the 6 pathotypes of DEC. In 394 children with diarrhea, 203 (52%) DEC infections were found. Among the 198 controls, 126 (63%) DEC infections were found. Enteroaggregative E. coli was the most common pathotype by multiplex PCR both in cases (58, 14.7%) and controls (47, 23.7%), followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
7
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 46 publications
5
52
7
8
Order By: Relevance
“…In Switzerland, a frequency of 8% of DEC was found among children with diarrhea [20], while among Caribbean-Colombian children, a rate of 14.4% was reported [26], and in Brazil, rates from 7.6% to 48% [11,[27][28][29][30] have been reported. In India, a frequency of 52% of DEC was found among children under five years of age with diarrhea [31], and in Ghana, these bacteria were recovered from 77% of children and 38% of adults with diarrhea [32]. These studies also showed that DEC are important causes of diarrhea.…”
Section: Discussionmentioning
confidence: 53%
“…In Switzerland, a frequency of 8% of DEC was found among children with diarrhea [20], while among Caribbean-Colombian children, a rate of 14.4% was reported [26], and in Brazil, rates from 7.6% to 48% [11,[27][28][29][30] have been reported. In India, a frequency of 52% of DEC was found among children under five years of age with diarrhea [31], and in Ghana, these bacteria were recovered from 77% of children and 38% of adults with diarrhea [32]. These studies also showed that DEC are important causes of diarrhea.…”
Section: Discussionmentioning
confidence: 53%
“…In a number of studies, EAEC has been isolated in almost equal numbers from patients suffering from diarrhea and from control groups (15,133,137). This finding has been proposed to be a result of acquired immunity (105,137) due to poor sanitary conditions as well as frequent exposure to pathogenic E. coli strains, resulting in the development of protective antibodies and colonization rather than infection.…”
Section: Discussionmentioning
confidence: 98%
“…The aggR gene is highly conserved among EAEC strains and has been found to be associated with diarrhea in several studies (105,133,154). A strong correlation between the CVD432 probe and the aggR gene has been reported (7,52,69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pediatric lethality index caused by diarrhea in Brazil is higher [29]. Gastrointestinal Infections (GIs) are among the leading causes of childhood mortality worldwide and are responsible for millions of deaths every year; India has surpassed Brazil (200.0000) [30][31][32]. Among the causative agents are several pathotypes of non-invasive Escherichia coli that cause diarrhea but do not produce heat-labile or heat-stable enterotoxins [33].…”
Section: Diarrhea Epidemiology and Pathogenesismentioning
confidence: 99%